Kajian Estetika Thomas Aquinas Pada Interior Kayu Aga House di Canggu Bali - Rosadi, Jessica (Intra, 2013)
Studies Aesthetics of Thomas Aquinas At Interior Kayu Aga House in Canggu Bali is a study that discusses the application of aesthetic theory of Thomas Aquinas. In residences Aga Wood House whose composition is unique building. Along the development, homes must also have a good composition so that residents can enjoy the beauty and comfort, because the houses were palaces for its inhabitants, and a place to rest after a day of activities. From the research that has been done, Kayu Aga House residence has a good aesthetic fit with the theory of Thomas Aquinas who said that beauty has three elements, namely the composition, proportion, and brightness (bright colors).